Quality of American Life, 1971 - Campbell, Angus ([Verlag nicht ermittelbar], 1984)
The purpose of this study was to survey Americans about perceived quality of life by measuring perceptions of their socio-psychological condition, their needs and expectations from life, and the degree to which those needs were satisfied. The data were collected via personal interviews from a nationwide probability sample of 2,164 persons 18 years of age and older during the summer of 1971. Closed and open-ended questions were used to probe respondents' satisfactions, dissatisfactions, aspirations, and disappointments in a variety of life domains, such as dwelling/neighborhood, local services (e.g., police, roads, and schools), public transportation, present personal life, life in the United States, education, occupation, job history/expectation, work life, housework, leisure activities, organizational affiliations, religious affiliation, health problems, financial situation, marriage (including widowhood, divorce, and separation), children/family life, and relationships with family and friends. In addition to broad questions about satisfaction with each of these domains and their importance to the respondents, specific sources of gratification and frustration are explored. Other questions focused on life as a whole and the extent to which respondents felt they had control over their lives (e.g., rating of various aspects of life, (dis)satisfaction with life, personal efficacy, and social desirability measures). Personal data include sex, age, race, ethnic background, childhood family stability, military service, and father's occupation and education. Observational data are included on housing and neighborhood characteristics as well as respondents' appearance, intelligence, and sincerity. An instructional subset of this study is also available (see ICPSR INSTRUCTIONAL SUBSET: QUALITY OF AMERICAN LIFE, 1971 [ICPSR 7516], also prepared by Campbell, Converse, and Rodgers.) It includes questions representative of the major areas covered in the original, longer survey. A related dataset, QUALITY OF AMERICAN LIFE, 1978 (ICPSR 7762), continues the survey conducted in 1971.